The state of mountain forest ecosystems in the Bashkir Nature Reserve (Southern Urals) - Biembetov Ainur; Yanybayev Nur; Valiev Ilnar (BIO Web of Conferences, 2021)
Environmental monitoring of specially protected natural reservations in Russia makes it necessary to analyze periodically the parameters of natural reservations to identify the state of components of nature. The Bashkir Nature Reserve is located in the Southern Urals. The availability of materials on forest management in 1956, 1969, 1979, and 2016 is one of the special features of the scientific fund of the Bashkir Nature Reserve. The analysis of these materials showed stable positive dynamics of the development of coniferous and small-leaved deciduous forestry and its current state.